2003
DOI: 10.1002/eqe.270
|View full text |Cite
|
Sign up to set email alerts
|

Empirical attenuation relationship for Arias Intensity

Abstract: SUMMARYArias Intensity is a ground motion parameter that captures the potential destructiveness of an earthquake as the integral of the square of the acceleration-time history. It correlates well with several commonly used demand measures of structural performance, liquefaction, and seismic slope stability. A new empirical relationship is developed to estimate Arias Intensity as a function of magnitude, distance, fault mechanism, and site category based on 1208 recorded ground motion data from 75 earthquakes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
144
2
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(166 citation statements)
references
References 25 publications
9
144
2
11
Order By: Relevance
“…where PGA is peak ground acceleration of the larger horizontal component, PGV is peak ground velocity (geometric mean), PGD is peak ground displacement (geometric mean), AI is Arias intensity (arithmetic mean) and RSD is relative significant duration (arithmetic mean), defined as the interval between the first exceedence of 5 and 95% of total Arias intensity [Trifunac and Brady, 1975]. Estimated PGA is from the model of Ambraseys et al [2005], estimated PGV is from the model of Campbell [1997], estimated PGD is from the model of Sadigh and Egan [1998], estimated AI is from the model of Travasarou et al [2003] and estimated RSD is from the model of Abrahamson and Silva [1996].…”
Section: Paris (Ipgp) Which Is Under the Aegis Of The Réseau Accélérmentioning
confidence: 99%
“…where PGA is peak ground acceleration of the larger horizontal component, PGV is peak ground velocity (geometric mean), PGD is peak ground displacement (geometric mean), AI is Arias intensity (arithmetic mean) and RSD is relative significant duration (arithmetic mean), defined as the interval between the first exceedence of 5 and 95% of total Arias intensity [Trifunac and Brady, 1975]. Estimated PGA is from the model of Ambraseys et al [2005], estimated PGV is from the model of Campbell [1997], estimated PGD is from the model of Sadigh and Egan [1998], estimated AI is from the model of Travasarou et al [2003] and estimated RSD is from the model of Abrahamson and Silva [1996].…”
Section: Paris (Ipgp) Which Is Under the Aegis Of The Réseau Accélérmentioning
confidence: 99%
“…In particular, the ability to reflect the energy of a groundmotion signal distributed across a broad frequency band or, equivalently, to reflect the influence of the entire duration of a ground motion is a property of Arias Intensity that lends itself to prudent application in many structural and geotechnical applications. Travasarou et al (2003) have demonstrated the effectiveness of using Arias Intensity as a predictor of the likelihood of damage to short-period structures, showing that the correlation between Arias Intensity and structural damage is, in this case, stronger than that between peak ground acceleration and structural damage. Arias Intensity is also a very useful ground-motion measure that can be used in geotechnical applications such as in the determination of the likelihood of rock falls and landslides (Harp and Wilson 1995;Del Gaudio et al 2003) or for estimating the susceptibility of a site to liquefaction (Egan and Rosidi 1991;Kayen and Mitchell 1997;Kramer and Mitchell 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In order to conduct hazard analyses in terms of Arias Intensity, stable empirical ground-motion models must be available for this purpose. However, in comparison with other measures of strong ground motion, there are very few models for Arias Intensity that could be used within a PSHA (Wilson and Keefer 1985;Keefer and Wilson 1989;Wilson 1993;Sabetta and Pugliese 1996;Travasarou et al 2003). Of the few models that are available, most must now be considered obsolete, as they do not make use of the large number of high-quality strong-motion records that have been compiled over the past decade or so.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kramer and Mitchell (2003), in studies for PEER, proposed the use of cumulative absolute velocity (CAV) as a parameter correlated with the development of excess pore water pressure and liquefaction in soils. Travasarou et al (2003), also in studies for PEER, proposed the use of Arias Intensity as a parameter correlated with damage to stiff systems such as shortperiod structures and stiff soil slopes. Both CAV and I a contain the effects of ground motion duration as well as amplitude because the parameters are summed over the duration of the time history.…”
Section: Record Characteristicsmentioning
confidence: 99%